FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA SEKTOR PERKEBUNAN - JULIANA YAPI; SATRIYO WIBOWO (Media Bisnis, 2019)
The purpose of this research is to test and analyze empirically the influence of profitability, firm size, liquidity, business risk, sales growth, asset structure and growth asset to capital structure. This research data consists of financial statements of plantation sector companies in Indonesia that listed in Indonesia Stock Exchange period 2008-2016. Sampling technique is used purposive sampling with 8 companies that met the criteria and were analyzed using panel data regression techniques with fixed effect model by using software Eviews 9 to test the hyphotesis. The results of this research shows that profitability, size, liquidity, business risk, and asset structure influence the capital structure, while sales growth and growth asset do not influence the capital structure. Where overall this model is fit.